com

DIFFERENTIATION
PREVIOUS EAMCET BITS 1.

x= 1)

1− y 1+ y

dy = dx

[EAMCET 2009]

4

( x + 1)

2

2)

4 ( x − 1)

(1 + x )

3

3)

x −1

(1 + x )

3

4)

4

(1 + x )

3

Ans: 2 Sol. Using Componendo and dividendo, then find y and
⎛ 1 ⎞ ⎛ t ⎞ dy −1 = 2. x = cos −1 ⎜ ⎟ , y = sin ⎜ ⎟⇒ 2 2 dx ⎝ 1+ t ⎠ ⎝ 1+ t ⎠ 1) 0 2) tan t 3) 1 Ans: 3 Sol. x = tan −1 t, y = tan −1 t
dy =1 dx
[EAMCET 2009]
4) 2

dy dx
[EAMCET 2009]

4) sint cost

⇒y=x⇒
3.

1 d ⎡ ⎛ x − 1 ⎞⎤ −1 ⎢a tan + b log ⎜ x + 1 ⎟ ⎥ = x 4 − 1 ⇒ a − 2b = dx ⎣ ⎝ ⎠⎦ 3) 0

1) 1 2) –1 Ans: 2 a b b 1 Sol. + − = 4 2 1+ x x −1 x + 1 x −1 a 2b 1 ⇒ 2 + 2 = 4 x +1 x −1 x −1 Put x = 0; a – 2b = 1 4.

⎧ dy ⎛ θ ⎞⎫ = If x = ⎨cos θ + log tan ⎜ ⎟ ⎬ and y = a sin θ then dx ⎝ 2 ⎠⎭ ⎩ 1) cotθ 2) tanθ 3) sinθ Ans: 2 dy dy dθ a cos θ Sol. = = dx dx ⎡ 1 ⎛ θ ⎞ 1⎤ a ⎢ − sin θ + × sec 2 ⎜ ⎟ . ⎥ dθ tan ( θ / 2 ) ⎝ 2 ⎠ 2⎦ ⎣

[EAMCET 2008]
4) cosθ

= − sin θ +

cos θ

1 ⎛θ⎞ ⎛θ⎞ 2sin ⎜ ⎟ cos ⎜ ⎟ ⎝2⎠ ⎝2⎠

=

cos θ

− sin θ +

1 sin θ

=

cos θ sin θ cos θ.sin θ = = tan θ 1 − sin 2 θ 1 − sin 2 θ

1

Derivatives

5.

If y = sin ( log e x ) then x 2
1) sin ( log e x )

d2 y dy +x = 2 dx dx 2) cos ( log e x )

[EAMCET 2008]
3) y2 4) – y

Ans: 4 Sol. y = sin ( log x ) ⇒ dy 1 dy = cos ( log x ) ⇒ x = cos ( log x ) dx x dx d 2 y dy 1 d2 y dy ⇒x 2 + = − sin ( log x ) ⇒ x 2 2 + x = −y dx dx x dx dx dy 6. If 2x 2 − 3xy + y 2 + x + 2y − 8 = 0 then dx 3y − 4x − 1 3y + 4x + 1 3y − 4x + 1 1) 2) 3) 2y − 3x + 2 2y + 3x + 2 2y − 3x − 2 Ans: 1 ∂f − dy 3y − 4x − 1 Sol. = ∂x = dx ⎛ ∂f ⎞ 2y − 3x + 2 ⎜ ∂y ⎟ ⎝ ⎠ ⎧⎛ 1 + x ⎞1/ 4 ⎫ 1 dy ⎪ ⎪ −1 If y = log ⎨⎜ = ⎟ ⎬ − tan ( x ) , then dx ⎪⎝ 1 − x ⎠ ⎪ 2 ⎩ ⎭ x x2 x 1) 2) 3) 4 2 1− x 1− x 1+ x4 Ans: 2
1/ 4

[EAMCET 2007]
4) 3y − 4x + 1 2y + 3x + 2

7.

[EAMCET 2007]
4) x 1− x4

1 ⎛ 1+ x ⎞ −1 Sol. y = log ⎜ ⎟ − tan ( x ) 2 ⎝ 1− x ⎠ 1 1 = ( log (1 + x ) − log (1 − x ) ) − tan −1 x 4 2 dy 1 ⎛ 1 1 ⎞ 1 x2 = ⎜ − − = ⎟ dx 4 ⎝ 1 + x 1 − x ⎠ 2 (1 + x 2 ) 1 − x 4 8. x = cos θ, y = sin 5θ ⇒ (1 − x 2 ) 1) – 5 y Ans: 4 Sol. 2) 5 y d2 y dy −x = 2 dx dx 3) 25 y 4) – 25 y
[EAMCET 2007]

dy −5cos 5θ −5 1 − sin 2 5θ = = dx sin θ 1 − cos 2 θ 1 − y2 1− x2 (1 − x 2 ) y12 = 25 (1 − y2 ) ⇒ (1 − x 2 ) y2 − xy1 = −25y y1 = −5

9.

x y = y x ⇒ x ( x − y log x ) 1) y ( y − x log y )

dy = dx 2) y ( y + l og y )

[EAMCET 2006]

3) x ( x + y log x )
2

4) x ( y − x log y )

Derivatives

Ans: 1 Sol. x y = y x ⇒ y log x = x log y dy ⇒ x ( x − y log ) = y ( y − x log y ) dx 10. If f : → is an even function which is twice differentiable on = 1) – 1 Ans: 3 Sol. Consider f ( x ) = f ′( x) = x2 2 2) 0 3) 1

and f ′′ (π) = 1, then f ′′ ( −π )
[EAMCET 2005]

4) 2

11.

2x = x, f ′ ( x ) = 1 2 f ′′ ( π ) = 1 = f ′′ ( −π ) Observe the following statements : f ′′ ( x ) I : f ( x ) = ax 41 + bx −40 ⇒ = 1640x −2 f (x) II :

[EAMCET 2005]

d 1 ⎛ 2x ⎞ = tan −1 ⎜ 2 ⎟ 2 dx ⎝ 1− x ⎠ 1+ x Which of the following is correct ? 1) I is true, but II is false 3) Neither I nor II is true Ans: 1 Sol. I) f ′′ ( x ) = 1640ax 39 + 1640x −42 .b
= 1640 1640 ax 41 + bx −40 ) = 2 f ( x ) 2 ( x x f ′′ ( x ) = 1640x −2 True f (x)

2) Both I and II are true 4) I is false, but II is true

⎛ 2x ⎞ II) ∴ tan −1 ⎜ = 2 tan −1 x 2 ⎟ ⎝ 1− x ⎠ d ( 2 tan −1 x ) = 1 +2x 2 false dx 12. f ( x ) = 10 cos x + (13 + 2x ) sin x ⇒ f ′′ ( x ) + f ( x ) = 1) cosx 2) 4cosx 3) sinx Ans: 2 Sol. f ′ ( x ) = −10sin x + (13 + 2x ) cos x + 2snix
f ′′ ( x ) = −10 cos x − (13 + 2x ) sin x + 2 cos x + 2 cos x = −f ( x ) + 4 cos x f ′′ ( x ) + f ( x ) = 4 cos x

[EAMCET 2005]

4) 4 sinx

3

Derivatives

13.

x 1+ y + y 1+ x = 0 ⇒ 1) 1

(1 + x )

2

2)

dy = dx −1
2

[EAMCET 2005]

(1 + x )

3)

1 1+ x2

4)

1 1+ x2

Ans: 2 Sol. x 1 + y = − y 1 + x x 2 + x 2 y = y2 + y2 x x 2 − y 2 = − xy ( x − y ) x + y = − xy −x −1 y= ⇒ y1 = 2 1+ x (1 + x ) 14. If f : → is an even function having derivatives of all orders, then an odd function among the [EAMCET 2004] following is ′ + f ′′ ′′ + f ′′′ ′′ ′′′ 1) f 2) f 3) f 4) f Ans: 2 Sol. f ′′′ is odd, since ‘f’ is even dy [EAMCET 2004] 15. x > 0, x y = e x − y ⇒ = dx 1) 1

(1 + log x )

2

2)

log x

(1 + log x )

2

⎛ log x ⎞ 3) ⎜ ⎟ ⎝ 1 + log x ⎠

2

4)

( log x )

2

1 + log x

Ans: 2 Sol. x − y = y log x ⇒ y = ⇒ dy log x = dx (1 + log x )2
[EAMCET 2003]

x 1 + log x

x −1 ⎧ for x ≠ 0 ⎪ 2 , then f 1 (1) = 16. If f ( x ) = ⎨ 3x − 7x + 5 ⎪ 1/ 3 for x = 1 ⎩ 1 2 1 1) − 2) − 3) − 9 9 3 Ans: 2 f ( x ) − f (1) Sol. f ′ (1) = lim = −2 / 9 x →1 x −1 x 17. If f ( x ) = for x ∈ then f 1 ( 0 ) = .... 1+ x 1) 0 2) 1 3) 2 Ans: 2 f ( x ) − f ( 0) Sol. f ′ ( 0 ) = lim =1 x →0 x

4)

1 3

[EAMCET 2003]
4)

4

Derivatives
18. Let f ( x ) = e x , g ( x ) = sin −1 x and h ( x ) = f ( g ( x ) ) , then 1) sin −1 x 2) 1
2

h′ ( x ) h (x)

= 4) esin
−1

[EAMCET 2002]
x

1− x Ans: 2 −1 Sol. h ( x ) = f ⎡ g ( x ) ⎤ = f ( sin −1 x ) = esin x ⎣ ⎦ h (x) = e ∴ h (x)
sin −1 x

3)

1 1− x2

⇒ h (x) =
1

esin

−1

x

h1 ( x )

1− x2

19.

1− x2 h′ ( x ) x If h(x) = e e then = h (x) 1) h(x) 2) 1 h (x) 3) log h(x)

=

1

[EAMCET 2001]
4) –log h(x)

Ans: 3 x Sol. Given h ( x ) = ee ⇒ log ( h ( x ) ) = e x ⇒ 20. h′ ( x ) = e x = log h ( x ) h (x)

If f ( x ) = 1) 4a Ans: 3

x2 then f ′′ ( a ) = x+a 1 2) 8a

[EAMCET 2001]
3) 1 4a 4) 8a

Sol. f ( x ) =

x2 a2 = x−a + x+a x+a 2 a f ′( x) = 1− 2 (x + a)

f ′′ ( x ) =

2a 2

(x + a)

3

∴ f ′′ ( a ) = 21.
x

2a 2

(a + a )
2

3

=

1 4a

If y = 22 , then 1) y ( log10 2 ) Ans: 3 y = 22x

dy = dx
2) y ( log e 2 )
2

[EAMCET 2000]
2 3) y2x ( log e ) 2

4) y log e 2

Sol.

2 ⇒ log y = 2 x log e

5